Changes and distributions of antibiotic resistance genes in liquid and solid fractions in mesophilic and thermophilic anaerobic digestion of dairy manure. Issue 6 (January 2021) - Zhang, Qiuping; Xu, Jifei; Wang, Xiujun; Zhu, Wenbo; Pang, Xiaoke; Zhao, Ji
Graphical abstract: Highlights: The changes of ARGs in LF and SF separately in AD were investigated. High TS enhanced ARG reductions in LF but promoted ARG enrichment in SF . The enriched ARGs in SF cause the irregular changes of ARGs in manure slurry. Abstract: This study mainly explored the changes and distributions of antibiotic resistance genes (ARGs) in liquid fraction (LF ) and solid fraction (SF ) in anaerobic digestion (AD) of dairy manure. After mesophilic and thermophilic AD, the copy numbers of ARGs in LF decreased by 0.06–1.80 logs while those in SF increased by 0.08–7.85 logs, suggesting the enrichment of ARGs in SF . Statistical analysis elucidated that high total solids promoted the enrichment of ARGs in SF . The increased abundances of genera such as Ruminofilibacter, Treponema and Sphaerochaeta in SF were responsible for the enrichment of most ARGs. These insights demonstrated the digested solid had the potential risks to promote the spread of ARGs in the environment, and the digested solid of livestock manure should be post-treated before the application.